2016
DOI: 10.3126/jmcjms.v3i2.16078
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dental Caries among adolescence of Dhanusha District, Nepal

Abstract: Background  and  Objectives:  In  developing  countries  like  Nepal,  the  oral  health  system  is currently  in  transition  phase  facing  a  high  prevalence  of  dental  caries.  It  has  significant  social impact in important life activities which hinders the achievement and ma intenance of good oral health  due  to  lack  of  dental  awareness  in  all  age  groups.  Streptococcus  mutans  is  the  most predominant  organism  to  cause  dental  caries.  Therefore, the  present  study  was  designed  t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
2
5
0
1
Order By: Relevance
“…The results of study done by Yadav K et al 8 in Dhanusha district, Nepal is almost similar to our results. They showed that the prevalence of dental caries was mostly in 15 to 19 years of females (66.32%) than males (39.70%).…”
Section: Discussionsupporting
confidence: 91%
“…The results of study done by Yadav K et al 8 in Dhanusha district, Nepal is almost similar to our results. They showed that the prevalence of dental caries was mostly in 15 to 19 years of females (66.32%) than males (39.70%).…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of dental caries was 55.84% among school going children of aged 6-12 years, which may be because of poor oral hygiene and consumption of junk food. Many studies found that prevalence and associated factors of dental caries among adult population was 33% [3]. Similar study, conducted at Nawalparasi, Nepal had reported that the oral health of the children was poor, chiefly dental caries remained widespread among children in school.…”
Section: Discussionmentioning
confidence: 82%
“…Dental caries is caused by imbalance between tooth minerals and biofilm which is also commonly known as plaque. Generally, dental plaque is caused by bacterial acid production and buffering action of saliva and surrounding tooth structures which ultimately causes demineralization of enamel, dentin and cementum of tooth structure resulting into dental caries [3]. After intake of carbohydrates, streptococcus mutans cause formation of acids that dissolves the minerals of enamel and dentine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Стандартна грешка (8,17), като само в един от тях се споменава за високо разпространение на кариеса по канините (20).…”
Section: интензитет на кариесаunclassified